2022
DOI: 10.1007/s13760-022-01872-w
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation as a treatment for Wilson’s disease with neurological presentation: a systematic literature review

Abstract: Introduction Wilson’s disease (WD) is a potentially treatable, genetic disorder of copper metabolism, with survival similar to healthy populations if controlled. However, in almost 50% of WD patients, neurological symptoms persist despite treatment, and in up to 10% of patients, neurological deterioration is irreversible. International guidelines on WD treatment do not recommend liver transplantation (LT) as a treatment for neurological symptoms in WD. However, such treatment has been assessed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…In our cohort, when comparing WD + OLTx patients to WD -OLTx patients, those who had undergone OLTx had a 58.68% reduction in inpatient mortality compared to WD patients who had not undergone OLTx. Other studies have also shown OLTx to improve mortality rates in patients with WD [23][24][25]. Liver transplantation is the only effective and functional cure for WD and is generally considered in patients with end-stage liver disease and/or fulminant hepatic failure who no longer respond to medical therapy [23,26].…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, when comparing WD + OLTx patients to WD -OLTx patients, those who had undergone OLTx had a 58.68% reduction in inpatient mortality compared to WD patients who had not undergone OLTx. Other studies have also shown OLTx to improve mortality rates in patients with WD [23][24][25]. Liver transplantation is the only effective and functional cure for WD and is generally considered in patients with end-stage liver disease and/or fulminant hepatic failure who no longer respond to medical therapy [23,26].…”
Section: Discussionmentioning
confidence: 99%
“…1 Clinical markers that have been associated with post treatment decline include: initial neurologic presentation (as opposed to hepatic presentation), higher UWDRS parts II and III scores, thalamic and brainstem pathology on MRI, and treatment with dopamine antagonists. 8 Additionally, elevated serum neurofilament light chain levels have been reported as possibly predict this early neurologic deterioration. 9 In a single center retrospective audit, penicillamine also caused significant hematologic and renal adverse events, with significant intolerance noted in 28 of the 112 patients studied.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of LT for neurologic WD showed a discrepancy between older and newer studies, with newer studies reporting better results of neurologic improvement and better survival rates. 8 A retrospective cohort study in 2020 looked at eighteen French patients ranging between 16-20.8 years of age who were resistant to decoppering agents and who underwent LT as rescue therapy for pure neurologic indications. Eight of these patients experienced a statistically significant improvement in their Unified Wilson’s Disease Rating Scale (UWDRS) score, decreasing on average by 78%.…”
Section: Discussionmentioning
confidence: 99%
“…However, variable neurological improvement was found among patients in this cohort after LT, regardless of brain MRI lesion pattern before LT and lesion evolution pattern thereafter. Based on their experience and supported by evidence on the adult population, 17,[21][22][23][27][28][29] the authors suggest that transplantation should not be denied to pediatric WD patients with neurological manifestations, given that all patients in this cohort displayed at least some degree of neurological improvement after LT. A recent systematic review by Litwin et al 30 analyzed the outcomes of LT in 302 WD patients with neurological symptoms and concluded that LT should be a treatment option for neurological WD patients, especially in patients with severe neurological symptoms, not responding to anti-copper treatment. Although the pediatric group was not specifically addressed, some of the articles reviewed included children, giving further evidence to support our results.…”
Section: Discussionmentioning
confidence: 99%